MicroRNA-33b, upregulated by EF24, a curcumin analog, suppresses the epithelial-to-mesenchymal transition (EMT) and migratory potential of melanoma cells by targeting HMGA2. Issue 3 (5th May 2015) - Zhang, Pu; Bai, Huiyuan; Liu, Gentao; Wang, Heyong; Chen, Feng; Zhang, Baoshun; Zeng, Panying; Wu, Chengxiang; Peng, Cong; Huang, Changjin; Song, Yang; Song, Erqun
Highlights EF24 suppressed melanoma migration and EMT. EF24 increased miR-33b expression and subsequently inhibited HMGA2 expression. EF24 suppressed melanoma EMT by targeting miR-33b. miR-33b knockdown or HMGA2 overexpression reverted EF24-mediated suppression of FAK, Src and RhoA activation. miR-33b knockdown or HMGA2 overexpression reverted inhibitory effect of EF24 on stress fiber formation.